ANALISIS EMERGY AKTIVITAS NELAYAN SKALA KECIL DI KABUPATEN CILACAP - Patria, Andreas D; Adrianto, Luky; Kusumastanto, Tridoyo; Kamal, M.Mukhlis; Dahuri, Rokhmin (Jurnal Perikanan dan Kelautan, 2014)
This research described the application of emergy analysis to evaluate the sustainabil-ity of small scale fisheries activities. An advantage of emergy analysis is the ability to quantify environmental and economic inputs and outputs on a common basis. In this study, we con-structed emergy accounts for the small scale Fisheries activities in Cilacap District. The result of EYR value indicates that small-scale fishing activities do not contribute to the balanced de-velopment of regional economy. The value of the ELR is very high, showing the large number of small-scale fishermen to the intensity of the use of fishing gear. The comparison between the results of the emergy environmental burden (ESI) fishing activities by small-scale fisher-men in Cilacap regency potentially unsustainable.